Research of a modern energy-saving model of the enclosing structure of civil buildings from efficient insulations - Asatov Nurmuhamat; Djurayev Uktam; Aliyev Mashrab; Sagatov Bakhodir; Abdurakhmonov Azizjon (E3S Web of Conferences, 2024)
This article examines a modern energy-saving model of the enclosing structure of civil buildings made of effective insulation materials, which varies with different physics and mechanical properties, and complex studies of operational properties and calculations using the developed model of thermal insulation durability made it possible to obtain predictive values of the durability of various types of thermal insulation materials in the construction of wall fencing and make suggestions according to rational areas of application, incl. depending on the degree of capital of the building and the service life of the enclosing structures